Answer:
x-8 if x>0
-8 if x=0
-x-8 if x<0
Explanation:
Given that that,
|(x-19)+11|
Case I:
If the value of x greater than 0. It means the value of x is positive.
So we plug x= +x in the above expression.
(+x-19)+11
=x-19+11
=x-8
x-8 if x>0
Case II:
If the vale of x is equal to zero.
We plug x= 0 in the above expression.
(0-19)+11
= -19+11
= - 8
-8 if x=0
Case III
If the value of x lesser than 0. It means the value of x is always negative.
So we plug x= -x in the above expression.
(-x-19)+11
= - x-19+11
= - x-8
-x-8 if x<0